ALIH KODE, CAMPUR KODE, DAN VARIASI BAHASA PADA PEMENTASAN WAYANG SASAK - Fendy Yogha Pratama; Cerianing Putri Pratiwi; Much. Nuril Huda (Pendidikan Bahasa dan Sastra Universitas Muhammadiyah Purworejo, 2023)
The term Wayang Sasak refers to the puppet that developed and was staged in Lombok, West Nusa Tenggara. This study aims to describe the form of code mixing, code switching, and language variations in Sasak puppet performances. The source of the data was taken from the Sasak puppet performance with a play entitled